The Path to Digitally Supported Business Models Through Servitization: The Study Of 16 Small and Medium-Sized Companies in Germany - Tobias SCHMALLENBACH; Matthias VOGEL; Giuseppe STRINA (Communications of International Proceedings, 2023)
The aim of this study is to gain a deeper understanding of digitisation processes and digitally supported business model development in small and medium-sized enterprises (SMEs). The focus is on the differences and specific characteristics that companies exhibit in the early stage and advanced stage of digitalisation. SMEs need to innovate to remain competitive in the digital age. This may involve developing digitally-enabled business models that use digital technologies to transform a company's products, services and business model in the long term. The subject of this study is the survey of a total of 16 companies. Twelve SMEs in the early stages of digitisation will be interviewed about the path of digitally supported business model development and a further four companies in the advanced stages to examine the dimensions of a business model, especially through servitisation. Through a method triangulation using semi-structured interviews in the first survey and expert interviews in the second survey, central differences are to be worked out. As a result, product-oriented SMEs with less advanced digital servitisation do not differentiate between the various specialist terms of digitalisation, but reduce digitalisation to the process level. However, digitalisation is a driver for economic growth and scaling of business models and was also perceived as such. In addition, companies are confronted with challenges, especially in the workforce, which not only has to bring the necessary know-how, but also has to experience the change in corporate culture. In particular, problems in the distribution of responsibilities could be identified through special functions in the company that are explicitly responsible for the digital transformation and thus make cooperation more difficult.